Teacher Professionalism in the National Education System: Analysis of Position, Duties, Rights, Obligations, and Competencies - Budihartono, Budihartono; Rosdiana, Rosdiana; Yuspiani, Yuspiani; Subhan, Alwan (Global Education Journal, 2025)
Teacher professionalism is a key factor in improving the quality of national education. Teachers play a role not only as implementers of learning but also as strategic actors in character formation, student potential development, and the achievement of national education goals. This article aims to comprehensively analyze teacher professionalism in the national education system, emphasizing the position of teachers, their duties and responsibilities, their rights and obligations, and their competencies as professional educators. This research method uses a qualitative approach with a library research approach. Data analysis was conducted using content analysis techniques by critically examining the substance of regulations and literature to identify the relationship between the normative framework and the practice of teacher professionalism in the context of national education. The results of the study indicate that teachers have been normatively recognized as professionals with a strategic position in the national education system. Teacher professionalism is reflected in the implementation of pedagogical duties, moral and social responsibilities, the proportional fulfillment of rights and obligations, and the mastery of four main competencies: pedagogical, professional, personality, and social. However, the implementation of teacher professionalism still faces various challenges, such as unequal working conditions, high administrative burdens, limited ongoing professional development, and educational policy dynamics that do not fully support strengthening the role of teachers. This article concludes that teacher professionalism is not only determined by the quality of individual teachers but is also greatly influenced by support from the education system as a whole.